"UPRegulation" of CD47 by the endoplasmic reticulum stress pathway controls anti-tumor immune responses - Katherine L. Cook; David R. Soto-Pantoja (BMC, 2017)
Abstract We recently demonstrated that targeting the unfolded protein response (UPR) protein GRP78 down-regulates CD47 expression, resulting in increased tumor macrophage infiltration and inhibited resistance to anti-estrogen therapy. We now show new data indicating that anti-estrogen therapy regulates CD47 expression and implicates its ligand, thrombospondin-1, in regulation of tumor macrophage infiltration. Moreover, GRP78 and CD47 co-expression is associated with poor prognosis in breast cancer patients, suggesting the existence of crosstalk between UPR and immunity that regulates therapeutic responses in breast cancer.